Robust sequential biophysical fractionation of blood plasma to study variations in the biomolecular landscape of systemically circulating extracellular vesicles across clinical conditions. Issue 10 (14th August 2021) - Vergauwen, Glenn; Tulkens, Joeri; Pinheiro, Cláudio; Avila Cobos, Francisco; Dedeyne, Sándor; De Scheerder, Marie‐Angélique; Vandekerckhove, Linos; Impens, Francis; Miinalainen, Ilkka; Braems, Geert; Gevaert, Kris; Mestdagh, Pieter; et al.
Abstract: Separating extracellular vesicles (EV) from blood plasma is challenging and complicates their biological understanding and biomarker development. In this study, we fractionate blood plasma by combining size‐exclusion chromatography (SEC) and OptiPrep density gradient centrifugation to study clinical context‐dependent and time‐dependent variations in the biomolecular landscape of systemically circulating EV. Using pooled blood plasma samples from breast cancer patients, we first demonstrate the technical repeatability of blood plasma fractionation. Using serial blood plasma samples from HIV and ovarian cancer patients (n = 10) we next show that EV carry a clinical context‐dependent and/or time‐dependent protein and small RNA composition, including miRNA and tRNA. In addition, differential analysis of blood plasma fractions provides a catalogue of putative proteins not associated with systemically circulating EV. In conclusion, the implementation of blood plasma fractionation allows to advance the biological understanding and biomarker development of systemically circulating EV.